Shapes and images (Leuven ; Paris ; Walpole)
xii, 234 sayfa
Keywords: “This collection of papers is dedicated to Herman Brijder upon his retirement from the University of Amsterdam. He is a renowned scholar in the field of Greek ancient pottery and his research is mainly concentrated on the so-called Siana cups, made in the middle of the 6th century BC at Athens. Twenty three colleagues, among which former students, wrote articles on diverse aspects of Greek pottery of the 6th and 5th centuries BC, especially on vases produced at Athens. Various contributions have been presented during a round table in Brijder's former working environment, the Allard Pierson Museum at Amsterdam. Subjects include the iconography of mythical figures, the depiction of animals, means of transport, the shapes of drinking vessels and the distribution of Athenian pottery in the Mediterranean. A few essays deal with related topics. As a whole, the volume is a representative overview of themes that matter in modern research of ancient Greek pottery.” --